Migration and the diffusion of knowledge in a globalized economy - Stefan Groot (European Regional Science Association (ERSA), 2011)
This paper considers diversity of the knowledge of expats as a complementary dimension of human capital that may generate spillovers. Such, often intangible, knowledge about foreign markets, management skills, and other complementary information may enhance the productivity of these expats, or the people who interact with them. However, due to a lack of knowledge about local culture and language, productivity may also decline. We explore an extensive set of microdata from Statistics Netherlands, and use an augmented Mincer approach to simultaneously identify the private and social returns to the presence of foreign knowledge workers. Private returns are found to be negative and statistically significant, while no evidence for - either negative or positive - social returns is found.
Keywords: 330